A várospolitika változása és az elővárosok helyzete Párizsban és Budapesten (1850–1949) - Keresztély, Krisztina (Tér és Társadalom, 1995)
The formation of the suburbs in the 19th century gradually transformed the structure of the towns. The outskirts, developing at an accelerating pace compared to the towns, had a bigger and bigger share in the provision of urban functions (the moving out of the industry, establishment of residences etc.). The mutual dependence of the town and its environs on each other, at the same time, did not go together with the uniform development of the two areas at that time: The suburbs grew in an isolated, disordered way. The only way to eliminate the contradiction was that the town itself should be responsible for the management of the development and the provision of infrastructure in the outskirts. The arrangement of the environs of the town was thus gradually the competence of urban policy, urban planning. This process that lasted for about a century took place parallel in Paris and Budapest, despite the fact that the development of Budapest – for geographical and historical reasons – was belated compared to Paris. In these two cities the transition of the urban policy and simultaneously the change in the situation of the suburbs can be divided into three periods: The period of the urban policy of power lasted in Paris from the 1850s to the turn of the century, in Budapest from the 1873 unification of the city to World War I. The formation of the suburbs took place in this period in both cities. The city leadership only considered the outskirts as „unloading places" at that time and it only relied on them if it was directly necessary for the development of the city. The urban policy supporting the exclusive power of the city can be identified with the name of Haussmann in both cities: The formation of the uniform city image, with giant squares and public buildings started in Budapest, after Paris, due to the effect of Haussmann. The second phase that lasted from the turn of the century to the 1930s in Paris, and to the end of World War II in Budapest, was a transition from the urban policy of power to the conscious urban policy. Urban policy now realised the significance of the suburbs, the first plans, ideas to arrange the development of the outskirts were made now. There were different reasons for the changes in the two cities: The issue of the arrangement of the suburbs emerged in Paris because of the social problems (especially the housing crisis) reinforced as a consequence of the Haussmann type urban policy, while in Budapest because of the administrative difficulties separating the suburbs from the city. Nevertheless, apart from the debates about the notions, no comprehensive practical results were achieved at that time, thus it was just this time when the suburbs had their most disordered development. The creation of the first general town arrangement acts (in 1932 in Paris and in 1937 in Budapest) can be considered as the start of the conscious urban policy in both cities. In Paris as soon as in 1934, in Budapest only in 1947 were the first general arrangement plans finalised. These handled the suburbs as uniform areas, divided into zones. With the formation of the conscious urban policy the problem of the uniform arrangement of the suburbs was solved. Still, the first general arrangement plan was not implemented in Budapest: In 1949 the socialist leadership of the city abandoned the programme. Instead, they annexed the inner suburban ring of Budapest to the city, without an arrangement plan. The chaiige in the direction of the Hungarian urban policy, the formation of new urban development models opposing the „classical" urban planning called a halt to the century-long parallel development of Paris and Budapest in 1949.